LEGAL ISSUES OF LIABILITY OF HOMEOWNERS - Vera Grigorievna Fedorova; Lily Shamilevna Muhazhinova (Гуманитарные и юридические исследования, 2021)
Activities of such a modern civil legal form of apartment building management, as association of homeowners has not only advantages, but also involves liability according to the legislation of the Russian Federation. For successful functioning of a homeowners’ association in the management of apartment buildings, it is necessary to perform one’s du-ties in a fair and proper way. In case of failure or improper exercise of these obligations direct legal liability ensues. Despite significant development of the legal basis of homeowners’ liaibility there are many problems and unresolved issues. Independent civil liability is one of the hallmarks of a legal entity, and respectively, a homeowners’ association. This characteristic is enshrined in the Civil code of the Russian Federation and the Housing code of the Russian Federation